GOOGLE SUITE FOR EDUCATION TRAINING FOR 21ST CENTURY LEARNING IN SMA NEGERI 1 JATINOM - Septiana Wijayanti; Eric Kunto Aribowo; Ana Setyandari; Wisnu Nugroho Aji; Krisna Pebryawan; Tasari Tasari (LPM Universitas Pasundan, 2020)
This google suite training activity is one form of community service activities which is done by the excellent team of LPPM Unwidha Klaten. This is aimed at teachers to prepare the 21st century skills. Before, the training activities took place, the team was conducted the observation and interview, so it was decided that the place for community service activities was SMA Negeri 1 Jatinom and it is carried out in three meeting session of training. The first meeting was training on google docs, google slides, and google sheets. The second meeting was google form and google drive. The third meeting was google site and google classroom. This training shows the enthusiasm of the participants to learn the 21st century skills. It can be seen by the participants who consistently follow and explore all the material in training. From the total of 66 participants, 70% of them have completed all the task which is given in the end of each training. Besides, the participants are considered capable in operating various google suite according to the material provided.